Moscas, metiches, and methodologies: exploring power, subjectivity, and voice when researching the undocumented. Issue 8 (14th September 2021) - Reyna Rivarola, Alonso R.; López, Gerardo R.
Abstract: In this essay, Gerardo R. López, a non-undocumented immigrant scholar, who has done extensive research with undocumented immigrant communities, has a conversation with Alonso R. Reyna Rivarola, an undocumented immigrant scholar with Deferred Action for Childhood Arrivals (DACA), who writes and researches issues of how undocumented immigrant students experience schooling from a critical situated stance. Their conversation explores a range of topics that interrogate the problematic nature of researching the self/other, while simultaneously examining the broader purpose(s) of research in the academy.